The ramen girl - Ackerman, Robert Allan; Murphy, Brittany; Blanchard, Tammy; Mann, Gabriel; Yamazaki, Tsutomu, 1936-; Momoi, Kaori (Chatsworth, CA : Image entertainment, 2009)
A young woman is abandoned in Tokyo by her boyfriend, and finds her niche working in a ramen house for a tyrannical chef.
Originally released as a motion picture in 2008.
Features: deleted scenes, alternate ending, trailer.
Brittany Murphy, Tammy Blanchard, Gabriel Mann, Tsutomu Yamazaki, Kaori Momoi.
MPAA rating: Not rated.
DVD, Dolby digital 5.1 surround.
In English with optional English or Spanish subtitles.
Keywords: Cookery -- Japan; Man-woman relationships; Japan -- Drama; Video recordings for the hearing impaired; Fiction films; Feature films